Ask Questions, Get Answers

Questions  >>  CBSE XII  >>  Math  >>  Matrices

Using elementary transformations, find the inverse of the matrix if it exists - $ \begin{bmatrix} 2 & -6 \\ 1 & -2 \end{bmatrix} $

1 Answer

Need homework help? Click here.
  • There are six operations (transformations) on a matrix,three of which are due to rows and three due to columns which are known as elementary operations or transformations.
  • Row/Column Switching: Interchange of any two rows or two columns, i.e, $R_i\leftrightarrow R_j$ or $\;C_i\leftrightarrow C_j$
  • Row/Column Multiplication: The multiplication of the elements of any row or column by a non zero number: i.e, i.e $R_i\rightarrow kR_i$ where $k\neq 0$ or $\;C_j\rightarrow kC_j$ where $k\neq 0$
  • Row/Column Addition:The addition to the element of any row or column ,the corresponding elements of any other row or column multiplied by any non zero number: i.e $R_i\rightarrow R_i+kR_j$ or $\;C_i\rightarrow C_i+kC_j$, where $i \neq j$.
  • If A is a matrix such that A$^{-1}$ exists, then to find A$^{-1}$ using elementary row operations, write A = IA and apply a sequence of row operation on A = IA till we get, I = BA. The matrix B will be the inverse of A. Similarly, if we wish to find A$^{-1}$ using column operations, then, write A = AI and apply a sequence of column operations on A = AI till we get, I = AB.
Given:$A=\begin{bmatrix}2 & -6\\1 &-2\end{bmatrix}$
Step:1 In order to use row elementary transformation we write as A=IA.
$\begin{bmatrix}2 & -6\\1& -2\end{bmatrix}=\begin{bmatrix}1 & 0\\0&1\end{bmatrix}A$
Step: 2 Applying $R_1\Rightarrow R_1- R_2$
$\begin{bmatrix}2-1 & -6-(-2)\\1 &-2\end{bmatrix}=\begin{bmatrix}1-0 & 0-1\\0&1\end{bmatrix}A$
$\begin{bmatrix}1 & -4\\1 &-2\end{bmatrix}=\begin{bmatrix}1 & -1\\0&1\end{bmatrix}A$
Step 3: Applying $R_2\Rightarrow R_2- R_1$
$\begin{bmatrix}1 & -4\\1-1 & -2-(-4)\end{bmatrix}=\begin{bmatrix}1 & -1\\0-1&1-(-1)\end{bmatrix}A$
$\begin{bmatrix}1 & -4\\0 &2\end{bmatrix}=\begin{bmatrix}1 & -1\\-1&2\end{bmatrix}A$
Step :4 Applying $R_2\Rightarrow R_2\times \frac{1}{2}$
$\begin{bmatrix}1 &-4\\0 &2/2\end{bmatrix}=\begin{bmatrix}1 & -1\\-1/2&2/2\end{bmatrix}A$
$\begin{bmatrix}1 & -4\\0 &1\end{bmatrix}=\begin{bmatrix}1 & -1\\1/2&1\end{bmatrix}A$
Step:5 Applying $R_1\Rightarrow R_1+4R_2$
$\begin{bmatrix}1+0 &-4+4(1)\\0 &1\end{bmatrix}=\begin{bmatrix}1+4(-1/2) & -1+4(1)\\-1/2&1\end{bmatrix}A$
$\begin{bmatrix}1 & 0\\0 & 1\end{bmatrix}=\begin{bmatrix}1-2 & 3\\-1/2&1\end{bmatrix}A$
$\begin{bmatrix}1 & 0\\0 & 1\end{bmatrix}=\begin{bmatrix}-1 & 3\\-1/2&1\end{bmatrix}A$
$A^{-1}=\begin{bmatrix}-1 & 3\\-1/2 & 1\end{bmatrix}$
Home Ask Homework Questions